Introduction to the 31st International Conference on Logic Programming special issue. Issue 4 (3rd September 2015) - EITER, THOMAS; TONI, FRANCESCA
Abstract : The 31st edition of the International Conference of Logic Programming (ICLP 2015) took place in Cork, Ireland, from 31 August 2015 to 4 September 2015, co-located with the 21st International Conference on Principles and Practice of Constraint Programming (CP 2015) and part of George Boole 200, a celebration of the life and work of George Boole who was born in 1815 and worked at the University College of Cork.